99 CHILDHOOD PERSPECTIVES OF PARENTAL YOUNG-ONSET DEMENTIA: A QUALITATIVE DATA SYNTHESIS. (25th October 2022) - Blake, C; Hopper, L
Abstract: Background: While it is less common, young onset dementia manifests at a significantly younger age (< 65). Many people with young onset dementia are parents; however, little is known about impact of the condition on children and young adults. A qualitative thematic analysis was conducted to synthesise the literature on the perspectives of children and young adults with a parent living with young onset dementia. Methods: Electronic databases were searched in order to identify all peer-reviewed literature in relation to the perspectives of children and young adults with a parent living with young onset dementia. A thematic analysis was conducted on the relevant literature. Results: The electronic database search resulted in 15 full texts articles. Four main themes with related subthemes emerged from the thematic analysis. The four main themes were: changing family dynamics; psychological and physical strain; stigma and coping strategies. Conclusion: The current synthesis outlines the perspectives of children and young adults with a parent living with young onset dementia. There is a significant lack of research in this area which adds to the stereotypical view of dementia as an older person's disease. This can lead to children and young adults being impacted by lack of awareness and stigma resulting in significant psychosocial problems. As the number of people living with dementia (including young onset) is set to increase, future research with children and young adults with a parent with young onset dementia is important in order to better support this cohort.